EXPLORING LEARNER AUTONOMY: A MIXED-METHODS STUDY OF ELT PRACTICES IN MULTILINGUAL CLASSROOMS (Lex localis - Journal of Local Self-Government, 2025)
Learner autonomy has gained prominence in English Language Teaching (ELT) as a pivotal element in fostering independent and lifelong learning skills. This mixed-methods study investigates the practices and perceptions surrounding learner autonomy in multilingual classrooms, emphasizing its practical implementation and theoretical underpinnings. The research was conducted in diverse classroom settings, incorporating both quantitative surveys and qualitative interviews with teachers and students. Results indicate that fostering learner autonomy significantly enhances student engagement and academic outcomes, particularly in linguistically diverse settings. The findings also reveal challenges, such as cultural influences, lack of resources, and teacher preparedness, that hinder the integration of autonomy-driven approaches. Strategies like collaborative learning, use of technology, and personalized learning plans emerged as effective in promoting autonomy among learners. This study bridges the gap between theory and practice by offering actionable insights for educators and policymakers to implement autonomy-focused pedagogy in multilingual environments. The implications underscore the need for teacher training programs and resource development tailored to diverse linguistic contexts. Future research could expand the scope to include longitudinal studies and specific age groups for a comprehensive understanding of autonomy's role in language acquisition.